ASSESSING THE ROLE OF DIGITAL MARKETING IN SMALL BUSINESS GROWTH - Reddy DN, Madhusudhan (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper examines the transformative potential of digital marketing for small business growth in India. By leveraging tools like social media marketing, search engine optimization (SEO), and e-commerce, small businesses can overcome traditional barriers to scaling and achieve competitive advantages. This study explores digital marketing’s benefits, challenges, and emerging trends, supported by case studies and secondary data. In addition, the role of government initiatives and future prospects for digital adoption in SMEs is discussed. Recommendations for training, infrastructure, and policy support are provided, emphasizing digital marketing as a key driver of inclusivity and economic growth.